OBJECTIVE QUESTIONS

Mark against the correct answer in each of the following:

Question 1:

Which of the following is a true statement?

(a) -4 > -3

(b) -4 < -3

(c) -4 and -3 are non-comparable

Solution:

(b) -4 < -3

Since 4 is greater than 3 , -4 is less than -3 .

Question 2:

2 less than -3 is

(a) -1

(b) 1

(c) -5

(d) 5

Solution:

(c) -5

2 less than -3 means the following:

= -3 – 2

= -5

Question 3:

4 more than -5 is

(a) 9

(b) -9

(c) -1

(d) none of these

Solution:

(c) -1

4 more than -5 means the following:

= -5 + 4

= -1

Question 4:

2 less than -7 is

(a) -9

(b) -5

(c) 5

(d) none of these

Solution:

(a) -9

2 less than -7 means the following:

= -7 – 2

= -9

Question 5:

7 + | -3 | = ?

(a) 4

(b) 10

(c) -10

(d) none of these

Solution:

(b) 10

7 + | -3 |

= 7 + (+3) (The absolute value of -3 is 3.)

= 7 + 3

= 10

Question 6:

(-42) + (-35) = ?

(a) -7

(b) 7

(c) -77

(d) none of these

Solution:

(c) -77

(-42) + (-35)

= -42 – 35

= -77

Question 7:

(-37) + 6 = ?

(a) -43

(b) -31

(c) 31

(d) none of these

Solution:

(b) -31

(-37) + 6

= -37 + 6

= -31

Question 8:

49 + (-27) = ?

(a) -73

(b) -31

(c) 22

(d) none of these

Solution:

(c) 22

49 + (-27)

= 49 – 27

= 22

Question 9:

The successor of -18 is

(a) -19

(b) 17

(c) -17

(d) 19

Solution:

(c) -17

In succession, we move from the left to right of the number line.

Question 10:

The predecessor of -16 is

(a) -15

(b)-17

(c) 15

(d) 17

Solution:

(b) -17

To find the predecessor of a number, we move from the right to the left of a number line.

Question 11:

The additive inverse of -5 is

(a) 5

(b) 0

(c) -4

(d) -6

Solution:

(a) 5

If we add the additive inverse of a number to the number, we get 0.

-5 + 5 = 0

Question 12:

– 12 – (-5) = ?

(a) -17

(b) -7

(c) 7

(d) none of these

Solution:

(b) -7

– 12 – (-5)

= -12 + 5

= -7

Question 13:

5 – (-8) = ?

(a) 3

(b) 13

(c) -3

(d) none of these

Solution:

(b) 13

5 – (-8)

= 5 + 8

= 13

Question 14:

The sum of two integers is -25. If one of them is 30 then the other is

(a) 55

(b) 5

(c) -55

(d) none of these

Solution:

(c) -55

Let x be the other integer.

x + 30 = -25

x = -25 -30

x = -55

Question 15:

The sum of two integers is 20. If one of them is -5 then the other is

(a) 25

(b) -25

(c) 15

(d) none of these

Solution:

(a) 25

Let the other integer be x

x + (-5) = 20

x – 5 = 20

x = 25

Question 16:

The sum of two integers is -13. If one of them is 8 then the other is

(a) -5

(b) -21

(c) 21

(d) none of these

Solution:

(b) -21

Let the other integer be x.

x + 8 = -13

x = -13 – 8

x = -21

Question 17:

On subtracting -8 from 0, we get

(a) -8

(b) 8

(c) none of these

Solution:

(b) 8

0 – (-8)

= 0 + 8

= 8

Question 18:

8 + (-8) = ?

(a) 16

(b) -16

(c) 0

(d) none of these

Solution:

(c)

8 + (-8)

= 8 – 8

= 0

Question 19:

(-6) + 4 – (-3) = ?

(a) -5

(b) -1

(c) 1

(d) none of these

Solution:

(c) 1

(-6) + 4 – (-3)

= -6 + 4 + 3

= -6 + 7

= 1

Question 20:

6 – (-4) = ?

(a) 2

(b) -10

(c) 10

(d) none of these

Solution:

(c) 10

6 – (-4)

= 6 + 4

= 10

Question 21:

(-7) + (-9) + 12 + (-16) = ?

(a) -20

(b) 20

(c) -12

(d) none of these

Solution:

(a) -20

(-7) + (-9) + 12 + (-16)

= -7 – 9 + 12 – 16

= -20

Question 22:

On subtracting 8 from -4, we get

(a) 4

(b) 12

(c) -12

(d) none of these

Solution:

(c) -12

-4 – 8

= -12

Question 23:

On subtracting -9 from -6, we get

(a) -15

(b) -3

(c) 3

(d) none of these

Solution:

(c) 3

We have:

– 6 – (-9)

= – 6 + 9

= 3

Question 24:

On subtracting -5 from 10, we get

(a) 5

(b) -15

(c) 15

(d) none of these

Solution:

(c) 15

We have:

10 – (-5)

= 10 + 5

= 15

Question 25:

(-6) x 9 = ?

(a) 54

(b) -54

(c) none of these

Solution:

(b) -54

We have:

(-6) x 9

= -(6 x 9)

= -54

Question 26:

(-9) x 6 + (-9) x 4 = ?

(a) -90

(b) 90

(c) -18

(d) 18

Solution:

(a) -90

(-9) x 6 + (-9) x 4

Using distributive law:

(-9) x (6 + 4)

= (-9) x (10)

= -90

Question 27:

36 \(\div\) (-9) = ?

(a) 4

(b) -4

(c) none of these

Solution:

(b) -4

36 \(\div\) (-9)

\(\frac{ 36 }{ -9 }\)

= \(\frac{ 36 }{ 9 \times (-1) }\)

= \(\frac{ 1 }{ -1 } \times \frac{ 36 }{ 9 }\)

= -1 x 4 = – 4